Criminal Careers Among Female Perpetrators of Family and Nonfamily Homicide in Australia - Eriksson, Liss (Journal of interpersonal violence, 2021)
Knowledge of women’s pathways to serious offending, including homicide, is limited. This study contributes to a small but growing body of literature examining the criminal careers of serious female offenders by using interview data with females convicted of murder or manslaughter in Australia to examine various dimensions of their criminal careers, specifically, prevalence, frequency, age of onset, duration, and offending variety. In particular, in this study we compared criminal career dimensions across women who had killed a family member (e.g., intimate partner, children) and those whose victims were not part of the family unit (i.e., acquaintances or strangers). Our findings reveal differences between female homicide offenders who kill within and outside of the family unit. Although both groups had comparable overall lifetime prevalence of self-reported participation in criminal offending, findings indicate that participation among the family group was typically at low levels of frequency, of limited duration, and with relatively little variety in categories of offending. The family group also reported lower contact with the criminal justice system compared with the nonfamily group, and were less likely to have experienced some form of criminal/legal sanction in the 12 months prior to the homicide incident. This suggests that women who kill family members are more “conventional” than their nonfamily counterparts, in terms of having low and time-limited (i.e., short duration) lifetime participation in criminal offending.